Alcohol pharmacokinetics, decision making and folk wisdom: A reply to Moxnes and Jensen (2009) - Moss, A.; Dyer, K.; Albery, I.; Allsop, Steve; Kypri, K.; Erskine, J.; Mackintosh, D. (Elsevier Ireland Ltd, 2010)
Moxnes and Jensen (2009) present a study of decision making under conditions of uncertainty using a computerised simulation of alcohol pharmacokinetics. In their article, they conclude that their findings challenge the ‘folk wisdom’ that advises against drinking on an empty stomach. We contend that this is a problematic conclusion for three reasons: (1) the study and findings presented in their paper are simply not sufficient to allow one to, even tentatively, draw such a conclusion; (2) the conclusion is contrary to basic pharmacological knowledge concerning alcohol absorption, metabolism and the implications for peak blood alcohol concentration; and (3) the implications for understanding the process of decision making while alcohol intoxicated are not considered in the study. The Moxnes and Jensen (2009) study did not involve alcohol administration and is therefore an examination of decision making in situations of uncertainty rather than a specific exploration of drinking-related decision making. Recent formulations of the effects of alcohol on cognitive processing would lead to different conclusions than those presented by Moxnes and Jensen (2009). We conclude by suggesting our understanding of the implications of the study.